The dynamics of intervention : regulation and redistribution in the mixed economy - Kurrild-Klitgaard, Peter (Advances in Austrian economics, 2005)
The majority of studies in this book are dedicated to an examination and re-appreciation of the insight of the Austrian school of economics. Another small section contains part of a long-running debate on Austrian business cycles between Walter Block, William Barnett and Gordon Tullock.